Ce-405: Evaluation of Quaternary Ammonium Catalysts for Transesterification of Triglycerides - Wan Mohd Hafizuddin, Wan Yussof (2012)
Biodiesel is produced by transesterification of vegetable oils or animal fats with alcohols usually lower alcohols such as methanol and ethanol, in the presence of a catalyst. Most commercial biodiesel processes use homogenous base catalysts, as they result in a rapid reaction and over 95% conversion. However, homogenous base catalysts cannot be economically recovered, and necessitate a glycerol neutralisation step and place a greater load on a number of downstream separation steps. Replacing liquid homogeneous catalysts with solid heterogeneous catalysts is expected to yield a cleaner product and result in lower production costs, as the catalyst will not have to be continually replaced. Separation of heterogeneous catalysts can be easily achieved using filtration. In this work, the catalytic performances of seven strong base type 1 anionic polymeric resins (PA306s, PA308, HPA25, DIX2, DIX4 and DIX8) with the functional group of –N(CH3)3+, are compared against tetramethylammonium hydroxide (TMAOH) in the transesterification of triacetin. The transesterifications were performed in well-mixed isothermal batch reactors at 60oC, 450rpm, with 6:1 methanol to triacetin molar ratio. Almost complete conversion was obtained when using TMAOH with concentration of 5.5 mmol/L, in less than 3 minutes. On reducing the concentration of TMAOH to 0.6875 mmol/L, the time taken to achieve nearly complete conversion was increased to 30 minutes. In comparison, about 90% conversion was achieved by the PA306s after 3 hours with the concentration of 5.5 mmol/L. Two of these resins, PA306s and PA308, gave above 95% conversion at 5.5 mmol/L after 6 hours reaction. No deactivation was observed on PA306s and A26 over five cycles. In addition, the residual activity studies showed that they did not leach. Although anionic polymeric resins are less active than the TMAOH, they have the potential to be developed and improved as heterogeneous catalysts for transesterification, as they are stable to leaching and maintain their conversion.